PENGGUNAAN MATEREIAL DIELEKTRIK BUATAN BERBASIS REKTANGULAR PATCH PADA ANTENA HORN UNTUK RADAR X-BAND - Chabesno S Panggabean; M. Reza Hidayat (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Dielectric materials play an important role in antennas in an effort to support data communication. The material used by the dielectric is usually not even one material, however, it is a combination of several dielectric materials. From the final simulation results, the antenna is obtained at a working frequency of 7.822 GHz with a return loss of -20.336 dB, a bandwidth of 830.6 MHz and a VSWR of 1.21. Whereas in the measurement results of the horn antenna using dielectric material that has been realized, it is found that the antenna is able to work at a frequency of 8.41GHz with a return loss of -13.31 dB, a bandwidth of 110 MHz, and a VSWR of 1.61. The difference in parameter results could be due to dimensional differences between the simulated antenna and the antenna that has been realized. The difference in parameter results could be due to dimensional differences between the simulated antenna and the antenna that has been realized. Measurements are not carried out in a closed room or specifically for measuring the antenna, thus allowing interference to the waves from the antenna being measured because the simulation results are made in ideal conditions.